(untitled) - Kennett, David (Australia, 2004)
A comprehensive reevaluation of the nature of economic systems across the globe, A New View of Comparative Economic Systems is today's choice for today's world. This exciting text is not merely a re-treading of an obsolete Soviet-oriented text, but a fresh, new, and comprehensive reappraisal of the nature and study of economic systems. A New View of Comparative Economic Systems defines a new approach and will set the standard for years to come in Comparative Economic courses.
Keywords: Comparative economics